A beginner's guide to tissue clearing. (March 2017) - Ariel, Pablo
Highlights: Tissue clearing allows imaging many millimeters deep in fixed tissue. Any research project using fixed samples more than a few tens of microns thick can benefit from tissue clearing. Sample size, the need for immunostaining and the need for lipid staining are key to selecting a clearing method. Abstract: The last decade has seen a proliferation of tissue clearing methods that render large biological samples transparent and allow unprecedented three-dimensional views of enormous volumes of tissue. For a scientist wondering whether these methods will be useful to address their research problems, it can be bewildering to sort through the ever-increasing number of papers introducing new clearing methods. Here, I provide a concise summary for the novice describing what tissue clearing is, which research problems it can be applied to, how to decide on a clearing method, and where the field is headed in the future.